Me, myself and the other: Melanesian and Western ideas on selfhood and recognition$nElektronische Ressource - Galuschek, Anita (2015)
In my thesis I argue for a philosophical-anthropological approach which enables investigations in empathy and care by opening up a window on the motivation of recognition. I show how biographies as narratives can help to understand the other within her or his own life-world, even if the life-world is the very part of our personality as a dividually conceived relational self. Therewith, personhood can be conceived in a new concept of personhood that is understood as a category of the human being endowed with a stronger focus on culturally and historically founded dividuality and relationality, instead of relying exclusively on individuality and subjectivity. To show this relational movement in our life-world, I introduce ‘the Melanesian’ worldview on personhood. This worldview assumes that we are holistically relational. Thus, it lets the perception of an objective world shift into a world of animated entities which become parts of the human. Other people are also part of our life, and, in this way, take part in the life-world − and thus in life. In consequence, the life-world as the place where humans get in touch with each other builds up the social community: others have a particular role just as we take part in their lives. Our relationship with others is related to certain tasks in the social community and to definitions of personality and character. In academia, it is common ground that increasing individuality causes an increasing claim to recognition, especially since Honneth’s revival and actualization of Hegel’s concept of recognition. It is also Honneth who is inseparably linked with the recent philosophical discussion about recognition. We are recognized and we recognize others both on a personal as well as on a social level. The leading question, still unsolved and at the same time unsolvably linked with the relationship of individual and society, is: why are we relying on recognition? In other words: how do we recognize me, my self, and the other? My approach of a self-based model of mutual recognition follows two methodological paradigms: hermeneutics and phenomenology. Unsurprisingly, the hermeneutical investigation of our self in relation to mutual recognition has to start at the current state of the recognition debate, and takes its way to the anthropological state of personhood- and self-debate. The phenomenological approach constitutes the second main basis for an approach to a self-based concept of mutual recognition. Also the connection of philosophical and anthropological approaches to identity, personhood, and self-recognition is very fruitful in the way of developing a holistic approach of mutual recognition. To support this, I connect Western approaches in the phenomenological and hermeneutical traditions as well as theories of narrativity and human biography with non-Western approaches (Melanesian concept of personhood) to elaborate and emphasize the intersection of both approaches. In consequence, the Cartesian Ego is rejected in favour of a decentral, cosmomorphic, and sociocentric approach to personhood. This anthropological approach is merged with a narrative concept of identity to emphasize the self-reflexive way of personal identity. Building on this set of philosophical and anthropological arguments, my purpose is to draw up a self-based model of mutual recognition which includes all stages of mutual recognition: recognition of one’s own identity, recognition of one’s own acting, recognition of others, and evaluative recognition. I begin this journey with preliminary remarks on recognition, person, and self by elaborating the state of the art in approaches to mutual recognition, the Anthropological notion of personhood, individual, and self, and their Philosophical notion. In the second part of my work, I show how these approaches compose a self-based model of mutual recognition. Here we receive the idea how we are recognized: through empathic understanding an act of knowledge is performed, in which the other is perceived and acknowledged as another human similar to ourselves. Therefore, empathic understanding, feelings of sympathy, care and solicitude, personal ethos, and theories of mind are related to mutual recognition. The definition of our being through empathy highlights our social wellbeing. By implication we refer to the recognition of others as constitutive of the community, since we recognize others and take care of them.
Keywords: Heidegger, Martin -- 1889-1976; Hochschulschrift